KNOWLEDGE MANAGEMENT SYSTEM USING KNOWLEDGE SHARING FOR SUSTAINABLE BATAM TOURISM - Refli Noviardi; Rifa’atul Mahmudah Burhan; Achiles Dwiakila Ramadhan; Ryadi Adias Fahli; Raynold Raynold (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2026)
Abstract: The development of sustainable tourism in Batam City faces several challenges. Knowledge and information related to tourism remain scattered among various stakeholders, resulting in suboptimal coordination. Knowledge sharing and collaboration among stakeholders remain limited, so best practices and experiences have not been fully leveraged. A Knowledge Management System (KMS) based on knowledge sharing is needed to support information exchange and the development of sustainable tourism. The methodology used in this study is the Knowledge Management System Life Cycle (KMSLC) approach combined with Design Thinking. The research steps included an evaluation of the existing infrastructure, the formation of a knowledge management team, knowledge collection, the design of a KMS prototype, and the development of that prototype. The results of the study indicate that a knowledge-sharing-based Knowledge Management System (KMS) prototype was successfully developed to meet the needs of tourists and tourism stakeholders in Batam City. The system built is capable of facilitating the management, storage, and exchange of knowledge among stakeholders in a more integrated manner. The implementation of the KMS also enhances collaboration and supports the decision-making process in the development of tourism products and services. These findings indicate that a KMS can serve as an effective solution in supporting sustainable tourism development in Batam City. Keywords: tourism, KMLC, Batam City, design thinking, knowledge management. Abstrak: Pengembangan pariwisata berkelanjutan di Kota Batam menghadapi beberapa tantangan. Pengetahuan dan informasi terkait pariwisata masih tersebar di berbagai pemangku kepentingan sehingga koordinasi belum berjalan secara optimal. Berbagi pengetahuan dan kolaborasi antar pemangku kepentingan masih terbatas, sehingga pengalaman dan praktik terbaik belum dimanfaatkan secara maksimal. Diperlukan Sistem Manajemen Pengetahuan (KMS) berbasis knowledge sharing untuk mendukung pertukaran informasi dan pengembangan pariwisata berkelanjutan. Metodologi yang digunakan dalam penelitian ini adalah pendekatan Siklus Hidup Sistem Manajemen Pengetahuan (KMSLC) yang dikombinasikan dengan Design Thinking. Langkah-langkah penelitian mencakup evaluasi infrastruktur yang sudah ada, pembentukan tim manajemen pengetahuan, pengumpulan pengetahuan, perancangan prototipe KMS, serta pengembangan prototipe KMS tersebut. Hasil penelitian menunjukkan bahwa prototipe Knowledge Management System (KMS) berbasis knowledge sharing berhasil dikembangkan sesuai dengan kebutuhan wisatawan dan pemangku kepentingan pariwisata di Kota Batam. Sistem yang dibangun mampu memfasilitasi pengelolaan, penyimpanan, dan pertukaran pengetahuan antar pemangku kepentingan secara lebih terintegrasi. Implementasi KMS juga meningkatkan kolaborasi dan mendukung proses pengambilan keputusan dalam pengembangan produk dan layanan pariwisata. Temuan ini menunjukkan bahwa KMS dapat menjadi solusi yang efektif dalam mendukung pengembangan pariwisata yang berkelanjutan di Kota Batam. Kata kunci: pariwisata, KMLC, Kota Batam, desain thinking, manajemen pengetahuan.